The Medieval Translator. Traduire au Moyen Age - Jenkins, J.; Bertrand, O. (Brepols, 2007)
[Fundamental to all translation work, the concept of “displacement” allows one to take into account the multiple successive states inhering in a single text, and to interpret these variations. Translation is, in effect, a form of transfer; more specifically, it involves a movement from one context to another, be it national, social, political, historical, linguistic or religious. The texts examined here illustrate, each in their unique way, the relationship between contextual change and audience. They are also the product of subtle interactions between a variety of elements, the result of which is a “reinvention” of their respective roles and uses over time. For example, a text intending to entertain may also have educational outcomes; a book of local miracles may attract pilgrims <span class=